Wacana Humor Dalam Meme Di Media Online: (Kajian Semantik-Pragmatik) - M. SYA'BANUL KHOIR SINULINGGA (Center of Language and Cultural Studies, 2022)
This research is humor in memes in online media, the study of pragmatic semantics. The method used in this research is descriptive qualitative research. The data in this study were taken from memes obtained from online media with several sites. The results obtained from this study are from as many as 30 memes originating from 3 meme sites in Indonesia, 4 themes were found with various topics in them. The four themes are sequential, namely social, political, legal, and religious themes. Of the 4 themes, social themes are the most common. Topics in this social theme include love, school, friendship, relationships with other people, and other social life. The topic that comes up the most is about love (although the frequency is the same as other topics in social life.